Peran Katekese Keluarga Sebagai Persekutuan Umat Beriman di Zaman Sekarang Menurut Dokumen Familiaris Consortio Artikel 51-54 - Wenseslaus Jugan; Heribertus A. Bugis; Charolus G. D. Santos; Yohanes Wilson B. Lena Meo (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2024)
The focus of this research is to delve into and re-understand the apostolic exhortation of Pope John Paul II regarding the document Familiaris Consortio, specifically articles 51-54. This document specifically discusses the role of Christian families in the dynamics of contemporary times. This theme is very intriguing to study because it is relevant to the current family situation. The aim of this research is to make the Familiaris Consortio document a guide to enhance the understanding and awareness of families in carrying out their vocation. As a "small" Church, the family carries out the main task of Christianity, which is to proclaim the Gospel integrated into the sacrament of marriage. This is quite relevant to address all the issues and challenges facing Christian families today, such as divorce, domestic violence, the influence of technology on relationship patterns, and access to quality education due to lack of facilities and economic limitations. The methodology used in this research is qualitative research with a literature study approach. This paper finds that the Christian family is a Church Fellowship responsible for proclaiming the Gospel, educating in faith, and being a tangible sign of God's love integrated into the sacrament of marriage. By living out its unique vocation, the Christian family can bring God's presence and create goodness together.